Anti-Retroviral Strategies for AIDS and Related Diseases - Mark A Wainberg; Andre Dascal; Jack Mendelson (Canadian Journal of Infectious Diseases)
The replication cycle of human immunodeficiency virus type 1 (HIV-1) and other retroviruses consists of four stages: attachment of the virus to specific receptors on the cell surface; uncoating of the viral nucleic acid and conversion to DNA; production of viral RNA and proteins; and assembly and liberation of progeny virus from the cell. Each of these steps represents a potential target for antiviral chemotherapy. Combinations of drugs which act against different steps in the viral replication cycle might be expected to have synergistic potential. Zidovudine (AZT) is the most widely used drug to date for impeding the replication of HIV-1. Although AZT therapy has been reasonably successful, it has not been free from toxicity. In addition, there have been several reports of isolation of AZT-resistant variants of HIV-1.